1992
DOI: 10.2151/jmsj1965.70.5_975
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Stratospheric QBO on ENSO Variability

Abstract: A hypothetical mechanism is described whereby the Quasi-Biennial Oscillation (QBO) of Zonal winds in the equatorial stratosphere actively modulates the timing of El Nino-Southern Oscillation (ENSO) events. The mechanism involves the meridional redistribution of deep convective activity throughout the tropical Pacific warm pool region in response to variable wind shear processes which are linked to the opposing phases of the QBO. Hydrostatic conditions favoring deep convective activity within approximately *7* … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
85
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 46 publications
1
85
1
1
Order By: Relevance
“…Van Loon & Labitzke (1988) described how solar flux influences various atmospheric parameters, depending on the phase of the QBO, revealing its modulating influence on global climate. Gray et al (1992) described how the easterly phase of the QBO can help initiate El Niño events, depending on the state of the 'warm pool' and annual cycle. The easterly phase of the QBO appears to play a role in initiating every second El Niño event.…”
mentioning
confidence: 99%
“…Van Loon & Labitzke (1988) described how solar flux influences various atmospheric parameters, depending on the phase of the QBO, revealing its modulating influence on global climate. Gray et al (1992) described how the easterly phase of the QBO can help initiate El Niño events, depending on the state of the 'warm pool' and annual cycle. The easterly phase of the QBO appears to play a role in initiating every second El Niño event.…”
mentioning
confidence: 99%
“…fall in various regions [Gray, 1984;Kane, 1995 [Gray et al, 1992b;Knaff, 1992;Angell, 1992]. Some of these are faint at best and are not generally accepted [Kane, 1992;Xu, 1992].…”
mentioning
confidence: 99%
“…Several mechanisms have been suggested as to how a link might proceed. Gray et al (1992b) found that wind shear near the tropopause associated with the QBO phase in the lowermost stratosphere affects deep convection in the warm pool area. Giorgetta et al (1999) and Huang et al (2012) argued that the change in static stability due to the temperature QBO might play a more important role.…”
Section: The Qbo Effect On Snow Covermentioning
confidence: 99%